Does radio tagging affect the survival or reproduction of small cetaceans? A test - Martin, Anthony Richard; Silva, Vera Maria Ferreira da; Rothery, Peter R. (Marine Mammal Science, 2006)
A long-term study of botos (inia geoffrensis) in the Brazilian Amazon permitted the comparison of survival and reproduction between 51 adults fitted with radio transmitters and an equal number that were captured and handled in the same way but released without a transmitter. For both sexes combined, 47 radio tagged botos (92.2%) survived at least three years after release compared with 42 (82.4%) without radios, equating to annual survival of 97.3% and 93.6% respectively. The difference was not statistically significant. Eight of 15 closely monitored radio tagged females were lactating at capture, and all their calves weaned successfully. Two that were pregnant at capture subsequently gave birth. The mean number of calves per year born to these 15 females after first release was 0.172 (SD = 0.107) and to 17 non-tagged was 0.174 (SD = 0.095), again a non-significant difference. These results indicate that the anchoring of packages to the dorsal fin of dolphins can be accomplished with no measurable impact on their subsequent survival or reproductive output. However, botos may be unusually robust to handling, and this study should not be used to justify using similar techniques on other species without customary caution, diligence, and expert guidance. © 2006 by the Society for Marine Mammalogy.
Keywords: Biotelemetry; Cetacean; Ecological Impact; Reproduction; Survival; Tagging; Amazon River; South America; Cetacea; Inia Geoffrensis